Fairtrade towns: Unpacking the dynamics of locally developed ethical retail geographies. Issue 117 (December 2020) - Samuel, Anthony; Peattie, Ken; Herman, Agatha
Highlights: Fairtrade Towns are a widespread contemporary retailing and marketing phenomenon. Fairtrade Towns advance ethical consumption via a sidestreaming place-based dynamic. Fairtrade Towns encompass mainstream, alternative retailing spaces and places. Fairtrade Towns mobilise local individuals and institutions in ethical provisioning. Abstract: One of the most significant recent developments in ethical retailing is the Fairtrade Towns initiative. Its emphasis on the promotion of Fairtrade consumption within entire urban landscapes, and the communities and organisations within them, represents a geography of consumption into which millions of consumers are actively or passively enrolled. This empirical research paper considers Fairtrade Towns as retail geographies that connect across scales, shaped by the local, and yet expressing ethics and care on a global scale. Within them, local activists are revealed to adopt a novel role as 'citizen marketers' promoting FT consumption by local consumers and institutions by both utilising their own social networks and adopting marketing practices more usually associated with industry professionals. The resulting evolution of Fairtrade Towns is shown to have passed through two stages. The first supporting the broader global 'mainstreaming' agenda of the FT movement, with the second more focused on a novel contribution of local 'sidestreaming' to horizontally interconnect a range of types of place within a locality. This process has enrolled novel types of place and space as components of a local ethical retail geography, but this is revealed to potentially generate both synergies and tensions across different types of local place and stakeholder.